Automation, Migration, and Development: Geography of Job Precarity in South Asia and North Africa - Bhattarai, Keshav; Adhikari, Ambika Prasad (NCWA Annual Journal, 2026)
This article examines how accelerating automation and the adoption of artificial intelligence (AI) in advanced economies reshape labor markets across the Global South through interconnected channels of production, migration, and remittances. Drawing on the theories and practices of economic geography, labor economics, and development studies, the analysis conceptualizes automation as a transnational shock that contracts demand for migrant labor while simultaneously amplifying employment precarity in labor-surplus economies. The article advances a geographically grounded framework linking technology adoption in core industries with labor displacement, youth unemployment, and urban labor saturation in South Asia and North Africa. It further highlights the macroeconomic vulnerabilities in developing countries arising from remittance dependence and the role of digital media in shaping youth mobilization and political unrest in their native countries. By integrating comparative regional field evidence with a technology–labor–space framework, the study contributes to economic geography by demonstrating how digital transformation reconfigures development patterns across regions and countries. The findings underscore the limits of technology-led growth strategies in labor-abundant contexts and call for employment-centered digital policies that are spatially differentiated and institutionally grounded